The Effect of Learning Methods and Confidence on Learning Outcomes High Jumping Skills - M. Sahib Saleh; Syahruddin Syahruddin; Muhammad Syahrul Saleh; Irmawati Irmawati (STKIP Muhammadiyah Kuningan, 2022)
Physical education teachers must pay attention to the basics of high jump number learning materials starting from creating, supporting, hovering and landing. The phases of the primary jumping technique are expected to be carried out with various variations of learning methods to solve problems and complete learning so that students do not get bored. The purpose of the study was to determine the increase in learning outcomes for high jump skills on the material that has been taught through the application of learning methods in terms of the level of confidence. This research method is a 2X2 factorial experimental method, with the treatment variable being the direct learning method and problem-solving learning method. In contrast, the dependent variable is the result of learning high jump skills, and the attribute variable is self-confidence. The confidence variable uses a self-confidence questionnaire instrument, while the learning outcomes of high jump skills test the movement process of high jump skills. The research data were analyzed by two-way ANOVA analysis with the help of the SPSS version 20.0 computer program. The results showed that 1) Overall, learning outcomes of high jump skills through the application of problem-solving learning methods gave better results than direct learning methods, 2) There was an interaction between learning methods with confidence in learning outcomes of high jump skills, 3) For students who have high self-confidence, the results of learning high jump skills through the application of problem-solving learning methods give better results than direct learning methods, and 4) For students who have low self-confidence, the results of learning high jump skills through the application of direct learning methods are as good as problem-solving learning methods.